2001
DOI: 10.1259/bjr.74.884.740767
|View full text |Cite
|
Sign up to set email alerts
|

CT findings in congenital anomalies of the spleen

Abstract: There is a wide range of congenital anomalies of the spleen. Some are common, such as splenic lobulation and accessory spleen. Other less common conditions, such as wandering spleen and polysplenia, have particular clinical significance. Radiologists need to be aware of the various congenital variants of the spleen in order to recognize clinically important anomalies and to avoid mistaking less significant ones for an abnormality. In this pictorial review, the embryology of congenital anomalies of the spleen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
156
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(163 citation statements)
references
References 8 publications
3
156
0
4
Order By: Relevance
“…The initial splenic primordia are then created as incisures on the left side of the dorsal mesogastrium. When the incisures fail to fuse, they create two or more spleens [8] . The blood flow of an embryo makes a transition from symmetric to asymmetric around the 25th d to determine the visceral sidedness, and it has been suggested that this is when cono-truncal anomalies and anomalies of atrioventricular canal occur [9] .…”
Section: Discussionmentioning
confidence: 99%
“…The initial splenic primordia are then created as incisures on the left side of the dorsal mesogastrium. When the incisures fail to fuse, they create two or more spleens [8] . The blood flow of an embryo makes a transition from symmetric to asymmetric around the 25th d to determine the visceral sidedness, and it has been suggested that this is when cono-truncal anomalies and anomalies of atrioventricular canal occur [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Dentro de las alteraciones del bazo que pueden representar pseudo-tumores adrenales se encuentran las lobulaciones esplénicas, el bazo accesorio o errante y la presencia de arterias o venas esplénicas tortuosas o dilatadas secundarias a hipertensión portal 4 . El bazo comienza su crecimiento en la 5ª semana de vida fetal a partir de una masa de células mesenquimatosas originada en el mesogastrio dorsal, siendo las alteraciones en su desarrollo las responsables de la aparición de hendiduras, lobulaciones, la generación de bazos accesorios y el fenómeno de "bazo errante" (wandering spleen) producido por fallas en el desarrollo de los ligamentos gastro-esplénico o espleno-renal, lo que determina un mesenterio esplé-nico largo con movilidad aumentada, lo que favorece la presencia de torsión aguda o crónica del bazo 5 . La presencia de bazos accesorios puede observarse hasta en un 10% de los individuos, ubicados habitualmente en relación al hilio esplénico o adyacentes a la cola del páncreas.…”
Section: Discussionunclassified
“…La presencia de bazos accesorios puede observarse hasta en un 10% de los individuos, ubicados habitualmente en relación al hilio esplénico o adyacentes a la cola del páncreas. Sin embargo, pueden encontrarse también a lo largo del recorrido de los vasos esplénicos, en los ligamentos gastro-esplénico o espleno-renal, dentro de la cola del páncreas, de la pared del intestino o del colon, en el omento mayor o el mesenterio, e incluso en la pelvis o en el escroto 5 . La detección y caracterización de los bazos accesorios es importante debido a 3 problemas.…”
Section: Discussionunclassified
“…1,9,10 CT is an imaging technique commonly used to evaluate gastrointestinal tract diseases including SMT, 11,12 and is useful in making a differential diagnosis of an accessory spleen. 2,10 Accessory spleens appear round or oval, and the attenuation is identical to that of normal splenic parenchyma both before and after administration of contrast medium in CT, 2,10 as observed in the present patient. EUS is a better modality than CT for differentiating between an SMT and an extrinsic compression lesion of stomach.…”
Section: Discussionmentioning
confidence: 99%